2001
DOI: 10.2135/cropsci2001.4151589x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Resistance to Multiple Races of Heterodera glycines in Soybean PI 89772

Abstract: Breeding soybean [Glycine max (L.) Merr.] cultivars for resistance to soybean cyst nematode (SCN) [Heterodera glycines Ichinohe] is the most efficient means to control this pest. Evaluating and developing new resistance germplasm sources for soybean breeding is very important to prevent SCN from race shifts and provide durable resistance in soybean. We evaluated a newly found germplasm, soybean plant introduction (PI) 89772, which is resistant to SCN Races 1, 2, 3, 5, and moderately resistant to Race 14. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 33 publications
3
50
0
1
Order By: Relevance
“…Também foi verificado que as médias das linhagens avaliadas não conseguiram alcançar a média do genitor resistente (0,6). A variação transgressiva também foi observada em trabalho realizado por YUE et al (2001a) em famílias F 2:3 , derivadas do cruzamento entre a PI89772 (genitor resistente) e a cultivar Hamilton (genitor suscetível), inoculadas e avaliadas com a raça 5 do NCS.…”
Section: Resultsunclassified
“…Também foi verificado que as médias das linhagens avaliadas não conseguiram alcançar a média do genitor resistente (0,6). A variação transgressiva também foi observada em trabalho realizado por YUE et al (2001a) em famílias F 2:3 , derivadas do cruzamento entre a PI89772 (genitor resistente) e a cultivar Hamilton (genitor suscetível), inoculadas e avaliadas com a raça 5 do NCS.…”
Section: Resultsunclassified
“…rhg1 was identified by classical genetic analysis as a recessive gene (Caldwell et al 1960;Arelli et al 1992) which seems to be common to major SCN resistance sources and provides the major portion of resistance to race 3 and race 14 (Concibido et al 2004). Major quantitative trait loci (QTL) for resistance have been mapped across many resistance sources, including Peking and PI437654, PI90767, PI88788, PI209332, PI89772, and PI404198A (Concibido et al 1994(Concibido et al , 1996(Concibido et al , 1997(Concibido et al , 2004Webb et al 1995;Chang et al 1997;Heer et al 1998;Prabhu et al 1999;Meksem et al 2001a;Yue et al 2001;Guo et al 2006a), producing several loci and interactions among them (Huang et al 1997;Meksem et al 2001a;Concibido et al 2004). The QTL conferring the greatest level of resistance mapped to a genomic region containing rhg1 in linkage group (LG) G (Concibido et al 2004;Guo et al 2006a), and QTL clusters on each end of LG G were confirmed by meta-analysis, a statistical method for assessing whether QTLs detected on a linkage group map in different studies are located on the same locus or linked (Goffinet and Gerber 2000;Guo et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of the sources of resistance studied, the resistance gene rhg1 was mapped as a QTL onto chromosome 18 (formerly linkage group [LG] G). This gene was mapped in the SCN resistance sources PI 437654 (Webb et al, 1995), PI 209332 (Concibido et al, 1996), Peking, PI 90763, PI 88788 (Concibido et al, 1997;Glover et al, 2004), PI 89772 (Yue et al, 2001), PI 88287 (Bassuner et al, 2001), and PI 404198A (Guo et al, 2006). In addition, research showed that PI 437654 and PI 88788 have different alleles at rhg1 (Brucker et al, 2005).…”
mentioning
confidence: 99%